Examination of trends in north-south inequality. - Chew, Ivan Joo Chye. (2008)
There is a large and persistent gulf between the living standards of the developed countries (North) and developing countries (South). In this study, we examine whether the North-South income gap has been narrowing between 1960 and 1995. Our sample consists of 162 countries and our primary data source is the Penn World Table, version 5.6.